A novel minimally invasive nonanatomical single‐bundle medial collateral ligament reconstruction technique with a short isometric construct Achilles tendon allograft: A surgical description with clinical and radiological outcomes in multiligament knee injury patients - Mohammadreza Minator Sajjadi; Alireza Mirahmadi; Vahid Alizad; Mohammedhasan Dabis; Ali Saeidi; Mohammad Movahedinia (Journal of Experimental Orthopaedics)
Abstract Purpose Multiligament knee injuries (MLKIs) involve various ligaments in the knee. Current double‐bundle anatomical reconstructions of the medial collateral ligament (MCL) increase the level of technical complexity, often resulting in the establishment of numerous bone tunnels and different fixation points with additional hardware. To overcome these limitations, we proposed a novel minimally invasive nonanatomical MCL reconstruction with one tibial tunnel in the metaphysis using Achilles allograft in the MLKI setting. Methods In a retrospective study, we enroled 24 patients with MLKIs who underwent a new single‐strand short isometric construct (SIC) nonanatomical MCL reconstruction during 2020 and 2021. We fixed an Achilles allograft in one tunnel in the distal femur on the medial epicondyle and one tunnel in the metaphyseal part of the tibia using interference screws at 2 cm below the joint line between the anatomical insertion of the superficial MCL and the posterior oblique ligament. The patients underwent clinical and radiological assessment at the last follow‐up, 1–2 years after the operation, including valgus stress radiographs, range of motion (ROM), Lysholm and International Knee Documentation Committee (IKDC) scores. Results The mean postoperative IKDC score was 77.8 (range, 50.1–86.6). The mean Lysholm score was 84.1 ± 11.9 (range, 96–59). The medial knee widening difference (i.e., mean side‐to‐side difference under valgus stress x‐ray) was measured to be 1.2 mm on average. Only two patients (8%) had ROM limitation of 20° in knee flexion, one of which had surgery failure. Results showed a significant statistical difference between the patients' outcomes according to the number of involved ligaments. Conclusions This novel SIC‐like technique with a single tibial metaphyseal tunnel demonstrated satisfactory patient‐reported outcome measures, valgus stress radiographs, ROM and a low rate of knee stiffness and graft failure. While the number of injured ligaments in MLKI patients significantly influenced the outcomes, the results remained acceptable across all patients. Level of Evidence Level IV.